Desain, Pengembangan, dan Implementasi Gerbang Pembayaran Berbasis Web dan Android di Objek Wisata Bukit Cinta di Kabupaten Semarang - Ayudya Sawitri; Nabila Kusumawardani; Helmy, Helmy; Sindung Hadwi Widi Sason (Journal of Engineering and Applied Technology, 2025)
Advances in information and communication technology have brought significant changes to various aspects of life, including the tourism sector. Bukit Cinta Tourist Attraction in Semarang Regency is one of the tourist destinations that continues to strive to improve its services to visitors. One of these efforts is to implement a web-based and Android payment gateway system. This study aims to design and develop a payment gateway system that can facilitate digital payment transactions for visitors to the Bukit Cinta Tourist Attraction. The system is designed to integrate various payment methods, such as bank transfers and digital wallets, thereby simplifying the process of paying for entrance tickets and various services at the tourist site. The research method used is the agile method, which includes planning, design, development, and testing phases. The results of the black-box testing indicate that the application interface functions well as planned. In the stress test, it was found that higher network speed availability improves application performance, and overall, the system can handle request loads effectively. It is hoped that the results of this research will contribute positively to Bukit Cinta Tourist Attraction in Semarang Regency by enabling ticket purchases to be made anywhere and generating accurate transaction data